Finnish youth's views on religious and worldview membership and belonging - Kuusisto, Arniika (Journal of Religious Education, 2016)
This study examines Finnish youths' views on religious and worldview membership and belonging through a mixed methods study (N = 825) on pupils in the age groups 12-13 and 15-16. Finnish society is an interesting context for examining the topic from several perspectives. The membership in the Lutheran Church is still around 70%, but Finns are among the most passive churchgoers in Europe. Although Finnish society has been a home for 'old' religious and worldview diversities for a long time, the 'new' diversities (Vertovec 2015) have only become more accentuated in the societal worldview landscape during the past few decades through global mobility, secularization, and the Finns' interest in new religious movements. The present generation of Finnish youth have developed their value systems in between old and new worldview diversities. The data include various examples of what the 'Lutheran-based secular' (Riitaoja et al. 2010; Poulter et al. 2015) societal hegemony can mean in the life worlds of children and youth, and how multifaceted and fluid the youths' views on religious and worldview memberships and belonging are.